Safety, Tolerability, and Outcomes of Enteral Nutrition in Extracorporeal Membrane Oxygenation. (19th October 2020) - Davis, Robert C.; Durham, Lucian A.; Kiraly, Laszlo; Patel, Jayshil J.
Abstract: Extracorporeal membrane oxygenation (ECMO) is a supportive care system for patients with respiratory or cardiac failure. Patients requiring ECMO are at risk for significant inflammation, prolonged hospitalization, and acquired malnutrition and sarcopenia. Societal guidelines recommend early enteral nutrition in critically ill patients; however, in this population, optimal timing and dose of nutrition remains unknown and fear of reduced splanchnic perfusion, delayed gastric emptying, and bowel ischemia poses a barrier to appropriate energy and protein intake. This narrative review intends to provide an overview of ECMO, highlight the rationale for nutrition support in this population, and review the safety, tolerability, and outcomes associated with enteral nutrition during ECMO.